Carotenoid cleavage in chromoplasts of white and yellow‐fleshed peach varieties. (29th October 2018) - Giberti, Samuele; Giovannini, Daniela; Forlani, Giuseppe
Abstract: Background: In peach fruit, carotenoid accumulation in the mesocarp causes the difference between yellow and white genotypes. The latter are generally characterized by a peculiar and more intense aroma, because of higher release of volatiles deriving from dioxygenase‐catalysed breakdown of the tetraterpene skeleton. The rate of carotenoid oxidation was investigated in peach ( Prunus persica L.) fruits harvested at various stages of development. Two couples of white and yellow‐fleshed isogenic varieties and an ancestral white‐fleshed genotype were analysed, which had previously shown to differ in Carotenoid Cleavage Dioxygenase 4 allelic composition resulting in various combinations of putatively active/inactive proteins. Results: Carotenoid bleaching activity was localized in the insoluble fraction of fruit flesh chromoplasts. Higher rates of trans‐ β‐apo‐8′‐carotenal than β‐carotene bleaching suggest that the first cleavage reaction is the rate‐limiting step. Consistently, HPLC analysis did not show the appearance of coloured intermediates in reaction mixtures. High levels of substrate breakdown were found during the initial phases of fruit development in all genotypes examined, whereas significant differences were evident during the second exponential growth phase and ripening onset. Also, the ratio of carotene versus carotenale utilization varied significantly. Conclusion: Pattern comparison among activity levels measured in vitro on chromoplast enriched fractions suggests that cleavage enzyme(s) other than Carotenoid Cleavage Dioxygenase 4 play a significant role in carotenoid breakdown during fruit development and ripening. © 2018 Society of Chemical Industry